Small-scale Automated Drip Circulation System - Yaw Obeng Okofo Dartey; Eno Boamah Osei Antwi; Maryam Munagah Bassit; Elizabeth Ayaw Oduro-Koranteng (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2021)
Hunger and Poverty are one of the major problems faced in Sub-Saharan Africa. To get rid of this problem in line with the aim of the sustainable development goals, there is the need to increase current production levels of food. This can be achieved by mechanizing farming systems and introducing technology to farming systems. This paper seeks to introduce an automation system that uses automated drip irrigation with a circulation system to efficiently use energy and avoid the amount of water wasted during farming activities to attempt to increase food production levels..